Bench Mark Survey Reports on Manavadar Block-Bombay Nowgong Block-Madhya Pradesh and Rajpur Block-Madhya Pradesh - Planning Commission (Planning Commission, 1957)
The Manavadar Block of the Manavadar-Vanthali-Keshod Community Project is located in Manavadar Taluk of the Sorath district in the erstwhile State of Saurashtra, now part of the Bombay State. The taluk comprises 49 villages and 3 towns and covers an area of 200 sq. miles. The population of the Block, as enumerated in the 1951 census, was 70,080, of which 29,489 or 42.1 per cent lives in towns. This high percentage of the urban population has a distinct bearing on the social and economic life in the region.
Planning Commission Programme Evaluation Organisation Government of India
Planning Commission Programme Evaluation Organisation Government of India